Meer dan Welgelegen: Abraham van der Hart en de familie Hope (Bulletin KNOB, 2008)
Pavilion Welgelegen in Haarlem was built in 1785-1792 as the country house of the fabulously rich Amsterdam citizen Henry Hope (1735-1811), partner of the internationally renowned commercial bank Hope & Co. Since 1930 the Pavilion has been the seat of the provincial authorities of North Holland. So far, it was assumed that the consul of the Kingdom of Sardinia in the Dutch Republic, Michel (de) Triquetti (1748-1821), had designed Welgelegen, whose plans were said to have been executed by Jean-Baptiste Dubois (1762-1851), an architect from Dendermonde.However, it has now been ascertained that the designer was Abraham van der Hart (1747-1820), town architect of Amsterdam at that time. This is the result of new research in the records, confirmed by the conclusions of a study of Henry Hope's network of relations in connection with known buildings of Van der Hart. Research of Pavilion Welgelegen itself showed that the L-shaped building originally consisted of two rather autonomous parts: a residential wing on the Dreef and a picture gallery on Haarlemmerhout. It also appeared that the residential wing is in fact the refurbished country house that Hope had bought in 1769. This functional distinction was also evident from the very expensive interior, for instance, the soft furnishings: chintz for the residential wing and silk for the gallery. The soft furnishings were the work of the French decorator Louis le Houx, who had probably settled in Haarlem especially for this assignment.Because of the imperfect connection between the wings it may be assumed that initially the design of the picture gallery on Haarlemmerhout was not intended for Welgelegen, but for the country estate Groenendaal in Heemstede, the property of John Hope, Henry's cousin. Just as Henry, John was a partner of Hope & Co, but he was a collector in the first place; around 1780 his collection of paintings was the most important of Amsterdam. Everything indicates that John had plans for the building of a picture gallery in his country estate, when he suddenly died in 1784.Henry Hope took over a large part of his paintings and commissioned Abraham van der Hart to make the design of this picture gallery suitable for Welgelegen. It is likely that this design had also been made by him, because there are indications that Van der Hart had already known the Hope family before. For instance, in 1784 the Hopes were the major investors in the building of the French Theatre in Amsterdam, of which Van der Hart was the architect; Pietro Antonio Bolangaro Crevenna (1736-1792), for whom Van der Hart had probably designed Nieuwezijds Voorburgwal 212 in 1782, also belonged to the circle of founders of this theatre and consequently to the circle of the Hopes. It is even possible that in 1777 Van der Hart was appointed town architect of Amsterdam through the mediation of John Hope, who had a seat in the town council, after all.His involvement in Pavilion Welgelegen resulted in a lot of commissions for Van der Hart as a private architect. He was asked for the construction/refurbishment of the country estate Wildhoef near Bloemendaal (around 1788), Herengracht 544 in Amsterdam (from 1789), the town house Huis Kops in Haarlem (Nieuwe Gracht 74, from 1790), Herengracht 509-511 in Amsterdam (around 1791), the town house Huis Hodshon in Haarlem (Spaarne 17, 1793-1796), the country estate Huis Doorn (around 1791-1795), the country estate Elsenburg near Maarssen (around 1795), the dome of country estate Bellevue in Haarlem (Kleine Houtweg 119, around 1801), and the town house Huis Barnaart in Haarlem (Nieuwe Gracht 7, 1803-1807). In the interiors of these buildings the influence of the work of Robert Adam is clearly to be recognized from 1789 onwards, which Van der Hart had become acquainted with during the construction of Welgelegen, probably through Henry Hope himself.Consequently, the Hope family meant a great deal for Abraham van der Hart, directly by its commissions, its patronage and its network of relations, as well as indirectly by the great interest Welgelegen attracted.